Build emotional attachment of freight forwarding company using social media interactivity, brand image, brand commitment, and halal awarness - Reza Maulana; E R Taufik; Lutfi Lutfi (Junal Ilmu Manajemen, 2023)
This reseacrh is to answer the effect of social media interactivity, brand image, brand commitment, and halal awarness for customer of freight forwarder company. The methode using quantitative and nonprobability sampling then data process by PLS. Findings of this reaserch describe of positive corelation and has impact between brand commitment and emotional attachment directly. No direct impact and no positive correlation between social media interactivity, brand image, and halal awarness to customer emotional attachment. Sample of this reaserch are food and baverages company, fast moving consumer goods, and pharmaceutical company, which has export and import that located in Jakarta, Bogor, Depok, Tangerang, and Bekasi area.